The Reconstruction of Indigenous Knowledge about Golobe (Hornstedtia alliacea) as a Natural Resource Conservation Study for Prospective Teachers' Scientific Literacy - Parmin Parmin; Fidia Fibriana (State Institute of Islamic Studies Imam Bonjol Padang, 2020)
This study intended to measure prospective science teachers' scientific literacy through a conservation course on a natural resource topic. The natural source as the research object was golobe, an endemic plant in Maluku which has been consumed as the traditional medicine by the local community, which was studied for its chemical properties. Golobe is believed to have the properties to cure diseases. The lab testing revealed that golobe contains alkaloids, flavonoids, terpenoids, steroids, polyphenols, antioxidants and antibacterial properties. The scientific knowledge based on the lab report was reconstructed using the Science Integrated Learning (SIL) model. The obtained laboratory test results were matched up with the indigenous knowledge of the golobe. The indigenous knowledge of local community on golobe was converted to be the scientific knowledge. Then, the result of reconstruction was applied as the basis of Conservation Education course material development. The research target included prospective science teachers joining the Conservation Education course. The assessed scientific literacy consisted of (1) knowing scientific questions; (2) exploring; (3) identifying scientific evidence; (4) laboratory work; (5) drawing up conclusions; (6) communicating, and (7) demonstrating. Prospective teachers have owned the seven components of scientific literacy after studying natural resource conservation materials. The research concluded that the use of the knowledge reconstruction of Golobe in the North Loloda Tribe, North Maluku, Halmahera Archipelago has an impact on the development of prospective teachers' scientific literacy.